Single-shot condensation of exciton polaritons and the hole burning effect - E. Estrecho (Nature Portfolio, 2018)
The mechanism for exciton-polariton condensation in the presence of an incoherent reservoir has been long debated. Here the authors demonstrate the role of the spatial hole burning in condensation of long‐lived exciton polaritons by imaging the condensates in a single-shot excitation regime.